1991
DOI: 10.1128/aac.35.4.736
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural alterations induced by ICI 195,739, a bis-triazole derivative with strong antiproliferative action against Trypanosoma (Schizotrypanum) cruzi

Abstract: The ultrastructural alterations induced in vitro by ICI 195,739, a recently developed bis-triazole derivative with potent antiproliferative effects on Trypanosoma (Schizotrypanum) cruzi, are reported. On epimastigotes, the triazole at its minimum growth-inhibitory concentration (0.1 ,uM) produced immediately (within 24 h) gross alterations in the organization of chromatin and the appearance of large electron-dense granules; at this time, many cells were binucleated, indicating a blockade in cytokinesis. At la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 36 publications
3
35
1
1
Order By: Relevance
“…The minimal concentration of albaconazole required to induce epimastigote lysis was 30 nM, which is 33 times lower than that of ketoconazole, D0870, or itraconazole and which is comparable to that of posaconazole, the most potent EBI known against this parasite. Furthermore, against the clinically relevant intracellular amastigote form, the minimal concentration required to eliminate the parasite was just 10 nM (16,17,29,30,31,32). These data suggest that albaconazole could be a good candidate for in vivo chemotherapeutic studies.…”
Section: Discussionmentioning
confidence: 75%
“…The minimal concentration of albaconazole required to induce epimastigote lysis was 30 nM, which is 33 times lower than that of ketoconazole, D0870, or itraconazole and which is comparable to that of posaconazole, the most potent EBI known against this parasite. Furthermore, against the clinically relevant intracellular amastigote form, the minimal concentration required to eliminate the parasite was just 10 nM (16,17,29,30,31,32). These data suggest that albaconazole could be a good candidate for in vivo chemotherapeutic studies.…”
Section: Discussionmentioning
confidence: 75%
“…14). In a previous study we observed the same type of mitochondrial alterations in T. cruzi epimastigotes and amastigotes treated with 22,26-azasterol (63), as well as in T. cruzi and L. amazonensis incubated in the presence of other EBIs such as ICI 195,739 (22), ketoconazole, and terbinafine (21,61). Taken together, these observations suggest that the presence of ergosterol and analogs is essential for the maintenance of a normal structural organization of the mitochondrial membrane in trypanosomatids, especially the inner one.…”
Section: Resultsmentioning
confidence: 82%
“…The main alteration was observed in the mitochondrion-kinetoplast complex, which showed intense mitochondrial swelling and some alterations in the mitochondrial membrane, such as its rupture at some sites, and an increase in the number of cristae. These alterations in the mitochondrion were observed in a previous study when L. amazonensis (35) and T. cruzi (10,11) were incubated with other ergosterol biosynthesis inhibitors, such as terbinafine, ketoconazole, and 22,26-azasterol. The presence of these changes in the mitochondrion of trypanosomatids treated with different ergosterol biosynthesis inhibitors suggests that the presence of ergosterol or 5-dehydroepisterol is essential for the preservation of a normal structural organization of the mitochondrial membrane in these parasites.…”
Section: Vol 48 2004 Azasterols As Antiparasitics 2943mentioning
confidence: 93%